Preferences of regular metal brackets among patients reporting to dental hospital- an institutional based retrospective study - FAREEN, H. FIRDUS; SRIRENGALAKSHMI (The journal of contemporary issues in business and government, 2020)
The technology used to make orthodontic products and materials has advanced at an exponential rate. Newer materials, methods, and designs are coming up on a daily basis. These products help the orthodontist to give the best functional and aesthetic results to the patient. Orthodontic brackets have evolved from Angle’s era to the MBT brackets followed by lingual brackets. These brackets have made the life of the orthodontists much easier. As technology is advancing many more newer materials and designs are coming forward. The aim of the study was to evaluate the frequency of use of regular metal brackets among patients reporting to dental hospital in chennai, in the period of June 2019- March 2020. The clinical records of 1362 patients undergoing orthodontic treatment were evaluated. The prevalence of patients treated with regular metal brackets according to sex, gender and the different types of orthodontic brackets were assessed. Chi-square test was used to determine associations between variables, while the chi-square test for trends was used to assess the frequency of patients treated with regular metal brackets in comparison to others. The most frequently preferred brackets by patients were the regular metal brackets (99.5%) in comparison to other types of brackets. There was no statistically significant difference in patients treated with regular metal brackets with respect to age and gender. Thus, it can be concluded that the regular metal brackets are still being widely chosen by patients undergoing orthodontic treatment. Hence, awareness of different types of brackets and their uses should be brought among patients undergoing orthodontic treatment.